Enhancing Third-Grade Student’s Learning Outcomes Through The Cooperative Team Game Tournament (TGT) Model Using Snakes and Ladders Media On Plane Figures - Hayati, Zikra; Nurmalina, Nurmalina; Faridy, Faizatul; Mutia, Rizka; Arita, Salfayana Putri (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
This study aims to enhance the learning outcomes of third-grade students on the topic of plane figures through the implementation of the Cooperative Learning Model Team Game Tournament (TGT) assisted by the Snakes and Ladders educational game. The research employed a Classroom Action Research (CAR) design conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 12 third-grade students of SDN Tanjung Selamat, consisting of 5 boys and 7 girls. Data were collected by observation for teacher and student activities as well as learning outcome tests. The results indicated a consistent improvement in both teacher and student activities as well as student achievement. Teacher activity increased from 58% in Cycle I (fair) to 79% in Cycle II (good), and 95% in Cycle III (very good). Student activity rose from 56% (fair) to 77% (good) and finally 92% (very good). Student learning mastery improved from 42% in Cycle I to 58.33% in Cycle II, and 83.33% in Cycle III, surpassing the minimum mastery criterion. These findings suggest that the implementation of the Cooperative TGT model with Snakes and Ladders media effectively enhances student engagement and learning outcomes in mathematics, particularly in understanding plane figures.